A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus - Santos, Jandir C. [UNESP]; Martins, João P.I.; Britto, Erika P.J.; De Moraes, Gilberto J. (Magnolia Press, 2017)
Only two species of Podocinidae Berlese, Podocinum pacificum Berlese, 1895 and Podocinum sagax (Berlese, 1882c), have been reported from South America, both from Brazil and Argentina. The objective of this publication is to provide morphological information about specimens from Brazil identified as Podocinum bengalensis Bhattacharyya, 1968, P. pa-cificum and P. sagax, to describe a new species (Podocinum tupinamba n. sp.), and to present a new characterisation of Podocinum, incorporating characteristics of the mites examined in this study and a reappraisal of the literature.
Keywords: Mite; Morphology; Taxonomy